A novel iridium(iii) complex for sensitive HSA phosphorescence staining in proteome research. Issue 26 (14th March 2018) - Wang, Yi; Huang, Huaiyi; Chen, Ge; Chen, Haijie; Xu, Tingting; Tang, Qian; Zhu, Hailiang; Zhang, Qianling; Zhang, Pingyu
Abstract : A novel iridium(iii ) complex (Ir1 ) for sensitive HSA staining is reported. It is simpler and less time-consuming than Coomassie blue. Abstract : We report a novel organo-iridium(iii ) complex (Ir1 ) for the selective and sensitive determination of human serum albumin (HSA). The phosphorescence ofIr1 is turned-on by HSA in the urinary system. Importantly, Ir1 is much simpler and less time-consuming for HSA staining than Coomassie blue in proteomics studies.